Acessibilidade digital na perspectiva dos cidadãos com deficiências: evolução e desafios - BERRÍO-ZAPATA, Cristian (2020)
Digital technologies are present in the daily lives of the majority of the Brazilian population and have significantly impacted the lives of people with disabilities (PCDs). This paper aims to discuss the main issues related to the evolution of accessibility, in which information and communication technologies (ICT) play a central role. Many advances were made as a result of the demands and struggles of the communities of PCDs, giving rise to public policies and special services. Some of these achievements and their expression in ICT will be reviewed. There, the work of the World Wide Web Consortium (W3C) and its Web Content Accessibility Guidelines (WCAG) will be recapitulated. Some examples from the blind and deaf communities will be analyzed, as an input to show the degree of complexity of the subject and the challenges that await. It concludes on the three major barriers to accessibility and the new perspective of the communities of PCDs, in which ICTs can worsen or unlock the achievement of autonomy and social articulation of the PCDs.